ISTINBATH NUSHUS AL-SUNNAH MELALUI PENDEKATAN TEKSTUAL DAN KONTEKSTUAL - Aba, Syukri (At-Tafkir, 2017)
Muslims agree that the Sunnah or Hadith is the source of Law in Islam, in particular the authentic hadith which is undoubtedly the end. But it appears that some of the practices of Muslims in the past seem dissimiliar by the authentic Hadith itself. Such things can be found and traced to various books of fiqh whether it is classical or contemporary. To answer this phenomenon, a search on the approach used by the fuqaha in the formulation of Islamic law, among which is most important is a textual and contextual approach. Then what does this textual and contextual approach mean? How do the jurists formulate the law of the hadith based on these two approaches? Simply put, the textual approach is the legal istinbath based on a text of a hadith, while the contextual is instinbath of law based on qarinah or an indication that there is another meaning of the text of a hadith. In his application, the fuqaha compares the order of command and prohibitions shigat in a hadith with indications indicating the existence of a specific purpose that imposes or abolishes the commands and prohibitions. If the order or prohibition is considered strong and clear, then it becomes a law enforcement. On the contrary, if an indication indicates a more specific purpose, then that is the purpose of the law enforcement.